Two new species of Coecobrya (Collembola: Entomobryidae: Entomobryinae) from China, with a key to the Chinese species of the genus - Xu, Guo-Liang; Yu, Dao-Yuan; Zhang, Feng (Zootaxa, 2012)
Two new species of the genus Coecobrya are described. Both species, belonging to tenebricosa-group, present smoothchaetae on manubrium and base of dens, three sutural cephalic chaetae, labial formula MREL 1 L 2 , spiny microchaetae Xand X 4 posterior to labium, large outer tooth on unguiculus, 3 inner ungual teeth, S-chaetotaxy formula 32/222–3, and 4+4central macrochaetae on Abd. IV. C. brevis sp. nov. is similar to C. tibiotarsalis, and differs from the latter by Abd. IVchaetotaxy and ventral tube. C. pani sp. nov. is similar to C. borerae but can be separated by the latter in chaetotaxy of Abd. III and IV. A key to the Chinese Coecobrya species is provided.